2007
DOI: 10.1111/j.1365-2044.2006.04943_3.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased administration of oxygen improves cerebral oxygenation during carotid endarterectomy

Abstract: Creation of an arteriovenous fistula is a common vascular procedure in patients with significant co-morbidities. Brachial plexus block is a safe alternative to general anaesthesia in these patients [1]. It has been shown that the regional sympathetic block associated with brachial plexus block produces a greater increase in brachial artery blood flow than general anaesthesia with less systemic hypotension [2]. Therefore we hypothesised that the favourable peri-operative haemodynamics under brachial plexus bloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…As a matter of explanation, an assumption is made that ipsilateral cerebral tissues are oxygen delivery dependent more than contralateral districts. Supporting this hypothesis, de Beer et al [12] reported that giving 100% oxygen during the clamping phase improves cerebral oxygenation without raising blood pressure. Our objection is that the choosing f i O 2 100% during carotid clamping may mask a deficit of perfusion in the non-monitored brain districts, giving a normal rSO 2 in the frontal lobes.…”
Section: Discussionmentioning
confidence: 88%
“…As a matter of explanation, an assumption is made that ipsilateral cerebral tissues are oxygen delivery dependent more than contralateral districts. Supporting this hypothesis, de Beer et al [12] reported that giving 100% oxygen during the clamping phase improves cerebral oxygenation without raising blood pressure. Our objection is that the choosing f i O 2 100% during carotid clamping may mask a deficit of perfusion in the non-monitored brain districts, giving a normal rSO 2 in the frontal lobes.…”
Section: Discussionmentioning
confidence: 88%